Detection of allelic variants in lactoferrin gene promoter using created restriction site PCR-RFLP and its association with mastitis - CHOPRA, ALKA; GUPTA, I D; VERMA, ARCHANA; VOHRA, V (The Indian Journal of Animal Sciences, 2014)
Incidence of mastitis may be associated with single nucleotide polymorphism (SNP). Cows (350) belonging to Sahiwal and Karan Fries were screened. Polymorphism of bovine lactoferrin gene promoter was determined by using created restriction site polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results indicated that lactorferrin gene promoter is polymorphic and showed varied levels of polymorphism among Sahiwal and Karan Fries cattle. Three genotypes were identified, viz. EE, EF and FF in Sahiwal cattle and EE genotype was absent in Karan Fries cattle. Association of SNP identified with incidence of mastitis using chi square test, revealed nonsignificant association with mastitis incidence.